A Tool for Toponym Recognition in Medieval Documents (Linguamática, 2019)
This paper describes a method to build a tool aimed at recognizing geographical named entities in medieval texts. The new tool has been developed using the corresponding modules for contemporary languages contained in LinguaKit, a suite of NLP tools. A collection of manually annotated corpora served as a resource to build a gazetteer of medieval toponyms and find patterns to improve and implement new rules for the recognition of place names. In addition to the gazetteer, a list of triggers was the most determinant factor to improve recall. Final adjustments considered the most frequent terms of the lexicon and grammatical contexts for geographical named entities. In the process of building a model of medieval language and a specific lexicon, the available tool can already be used to annotate texts and shows a significant improvement when compared with previous modules. However, most work remains to be done in terms of adding specific gazetteers for entities other than
Keywords: georeferential entities; detection of toponyms; named entity recognition